Experiment and simulation investigations on W/Cu components prepared by strong confinement thermal explosive welding. (December 2021) - Lei, Mingzhun; Yang, Ming; Ni, Xiaojun; Ma, Honghao; Xu, Shuling
Highlights: A strong confinement thermal explosive welding was proposed for W/Cu composite. The high-quality W/Cu joint specimen without damage and defects was obtained. The microstructural evolution mechanism of the bonding interface was revealed. Abstract: The first-wall materials and components are the most thermally loaded in-vessel components of a fusion machine, which are required to survive at high heat fluxes induced by the intense plasma bombardment. As a candidate material, the W/Cu composite was investigated from the aspects of choosing a feasible and preferable welding method for high performance and high strength. For this, a strong confinement thermal explosive welding technology was proposed to solve the key problems in producing high-quality W/Cu composite material without damage and shock-induced defects. The microstructural evolution of the welding interface was observed and analyzed in the paper. Combining with the numerical simulation, the evolution mechanism of the bonding interface and the changing rule of the grain structure of the material were studied. This comprehensive research allows to provide a new perspective for preparing high-quality W/Cu composite.